Fundamentals of memory: applications to memory for sexual assault - Davis, Deborah (2025)
Though well-established principles of memory operate for events of all sorts, sexual events typically bring up a host of rather unique issues concerning the vast array of relevant information to be remembered and the personal and situational contexts in which sexual events take place. This chapter reviews the effects of specific situational and personal contexts relevant in many sexual situations on the attentional and interpretive functions of memory: and further discusses some complexities regarding the effects of emotions and the role of trauma that have been insufficiently considered in the literature on memory for sexual assault.